An eames primer. - Eames, Demetrios, ....- (New York : Universe Publishing, 2001)
Imbued with a strong core philosophy, Charles and Ray Eameses' work was very wide-ranging: from architecture and furniture to exhibition design and filmmaking. Eames Demetrios (grandson of Ray and Charles Eames) has written this introduction to their work. He shares anecdotes, previously unpublished photographs, and interviews with friends and colleagues of the Eameses. Also included is a directory of all Eames furniture, the manufacturers of these items through the years, and identification tips for collectors.
Keywords: Industrieel ontwerpen